An efficient temporal verification algorithm for intersectant constraints in scientific workflow. (3rd September 2019) - Wu, Lei; Li, Longshu; Li, Xuejun; Wang, Futian; Yang, Yun
It is usually essential to conduct temporal verification in order to ensure overall temporal correctness for the usefulness of execution results in a scientific workflow. For improving the efficiency of temporal verification, many efforts have been dedicated to the selection of more effective and efficient checkpoints along scientific workflow execution so that temporal violations can be found and handled in time. Most of checkpoint selection strategies involve temporal constraints, but the relations among the temporal constraints have been ignored. The only existing strategy considering relations among temporal constraints is for the nested situation and temporal dependency based only. However, the intersectant situation and non-dependency relationship of temporal constraints have to be considered. In this paper, a constraint adjustment strategy-based algorithm for efficient temporal verification in scientific workflow involved in both temporal dependency and temporal reverse-dependency is presented for the intersectant situation. Simulations show that the temporal verification efficiency of our algorithm is significantly improved.